Efficacy of CTPV for Diagnostic and Therapeutic Assessment: Comparison with Endoscopy in Cirrhotic Patients with Gastroesophageal Varices - Zijin Cui; Haiqing Yang; Xiaoxu Jin; Huiqing Jiang; Wei Qi; Wenfeng Feng; Zhijie Feng (Gastroenterology Research and Practice)
Background and Aims. Computed tomography portal venography (CTPV) shows potential in detecting varices that need treatment and their drainage pathways. However, its agreement with endoscopy requires further study. We investigated the feasibility of CTPV as an alternative tool to endoscopy in screening gastroesophageal varices (GEVs) and developed a CTPV-based model to provide a less invasive assessment of endotherapy for cirrhotic patients with GEVs. Methods. The study included 33 cirrhotic patients with a recent history of variceal hemorrhage. The presence, grade, and classification of GEVs on endoscopy and CTPV were compared (kappa test). Twenty-four patients were treated endoscopically, including 12 for esophageal varices (EVs), 8 for gastric varices (GVs), and 4 for GEVs. Treatment efficacies were assessed with the newly developed CTPV-based method at 1 week and 1 month after treatment. Efficiency evaluated by CTPV and endoscopy was compared by Fisher’s exact test to determine whether CTPV is efficient in the assessment of endotherapy efficacy. Results. For the screening and grading/classification of EVs and GVs, substantial agreement (EV kappa: 0.63 and 0.68; GV kappa: 0.62 and 0.75, respectively) was noted between endoscopy and CTPV. The therapeutic efficacy of EVs was higher when assessed by CTPV than when evaluated by endoscopy (37.50% vs. 12.50% at 1 week postoperation, P=0.22; 62.50% vs. 25.00% at 1 month postoperation, P=0.07), but without statistical significance. The same trend was also found in the assessment of therapeutic efficacy for GVs (25.00% vs. 16.67% at 1 week postoperation, P=1; 58.33% vs. 41.67% at 1 month postoperation, P=0.68). Conclusion. CTPV is comparable to endoscopy in the detection of GEVs and in the evaluation of endotherapy efficacy, which suggests that it could be a less invasive alternative for endoscopy in cirrhotic patients with GEVs needing treatment.